ANALISIS CONJOINT FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU BANK PERKREDITAN RAKYAT (BPR) DI KOTA SEMARANG DALAM PENILAIAN KREDIT MODAL KERJA - Diajeng Sarsa Putranto; Erman Denny Arfinto (JURNAL STUDI MANAJEMEN ORGANISASI, 2014)
Banking industry has the biggest influence in the economy of a country, that is acceptingfunds from the community in the form of savings and channeling back to the community inthe form of credit. According to Bank Indonesia, Rural Bank industry shows qualitygrowth of lending working capital. Along with the growth in working capital loans madeby Rural Banks, will most likely be followed by an increase in bad loans. The purpose ofthis research is to analyze how to reduce the risk of bad loans, then to know the factorsthat influence the behavior of Semarang Rural Bank in assessment of working capitalloan which were reviewed based on variable profit (net profit margin), leverage, networking capital, the value of the collateral, omzet as a proxy of firm size, and salesgrowth.Object of this study is Account Officer of Rural Banks in Semarang as much as 60Account Officers are taken from 15 Rural Banks. The type of data collected is primarydata and secondary data. The analytical method used was conjoint analysis to determinevalue preferences of each Account Officer Rural Bank in Semarang.Based on the research results for conjoint analysis shows that profit (net profit margin),net working capital, the value of the collateral, omzet as a proxy of firm size, and salesgrowth has positive effect on the behavior of Rural Bank in Semarang in the assessmentof working capital loans, while leverage has negative influential. The rank of preferencevalue according to all respondents are collateral is in first place with importance valuesof 40.883%, sales growth are second at 15.985%, net working capital was third at14.263%, payable on the fourth of 12.584%, profit in fifth at 9.266%, and the last isomzet that is equal to 7.020%.Keywords: Assessment of Working Capital Loan, Rural Bank, Account Officer, ConjointAnalysis